Pseudotumor cerebri syndrome in children with systemic lupus erythematosus: case series and review - Taha Moussa; Moussa Abdelhak; Cuoghi Edens (BMC, 2022)
Abstract Background Systemic lupus erythematosus (SLE) is a chronic autoimmune inflammatory disease that typically affects multiple organs and can lead to potentially fatal complications. Central nervous system (CNS) involvement in SLE is common, especially in children, and can present nonspecifically with various neuropsychiatric manifestations, described as neuropsychiatric SLE (NPSLE). Chronic headache is a common feature of NPSLE, secondary to increased intracranial pressure (also called pseudotumor cerebri (PTC)) due to inflammation or medication. Here, we highlight the importance of evaluating refractory headache (HA) in SLE patients to rule out PTC as a cause of severe morbidity. Methods Single tertiary care pediatric center case series of 8 children who developed NPSLE in the form of intracranial hypertension at or after SLE diagnosis. Conclusion Neurologic and ophthalmologic evaluation of refractory HA in patients with SLE, especially children, is warranted to decrease the burden of the disease and rule out treatable causes like PTC.